Case Studies on Enhanced Heat Transfer in a Square Duct with Modified V-Shaped Ribs (MVR): A CFD Analysis - Amnart Boonloi; Withada Jedsadaratanachai (Modelling and Simulation in Engineering)
This research presents structural improvement of V-shaped ribs for a tested square duct (TSD). The V-shaped ribs, which are inserted at the middle of the TSD (called type A), and the V-shaped ribs, which are placed on the opposite TSD walls (called type B), are modified to increase the structural stabilization. The effects of rib height to duct height, b/H=0.05–0.30; V-shaped bar thickness to duct height, a/H=0.025 and 0.050; and flow directions (V-Upstream and V-Downstream) are considered. The new design of the V-shaped ribs is called “modified V-shaped ribs or MVR.” The present problem is solved by the numerical method (commercial code). The flow and heat transfer features of the TSD are illustrated. The numerical result reveals that the MVR give both flow and heat transfer patterns similarly as the general V-shaped rib. The impinging flows, swirling flows, and disturbing thermal boundary layer, which lead to enhanced heat transfer, are observed. Over the investigated range, the enhanced heat transfer about 18.12 times above the smooth duct with the optimal thermal enhancement factor about 4.16 is detected.